(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article depicts the Khorezm epic, which is a genre of literature and musical reality distinguished by its long ancient background, unique style, dialect, and attractive melodies of narration as in other nations. It has been mentioned that Khorezm epics are mixed with narrative and poetry, and in some cases, they are expressed only in poetic form. The difference between Khorezm epics and other genres is in their breadth of lyrics, pleasant and sonorous music, smooth climaxes, and unique preludes.